The Element of Commitment as a Catalyst to Amal Jama’i Concept (Teamwork): A Study on Al-Wahida Marketing Sdn. Bhd. Entrepreneurs - Abdul Rahman, Mohd Nizho; Abdul Hamid, Solahuddin; Md Zain, Azman; Ghazali, Norzaliza (Institute for Political and international Studies (IPIS) of Iran, 2021)
This study focuses on a management issue that involves commitment as a catalyst to the concept of teamwork. One of the most talked about issues in an organization at present is about ineffective teamwork that is often caused by a lack of commitment in the discharge of the tasks entrusted. Hence, this study aims to identify the element of commitment as a catalyst to teamwork among the staff at al-Wahida Marketing Sdn. Bhd. For the study, both qualitative and quantitative methodologies are employed to investigate the issue of teamwork, and commitment, as one of the main elements. The findings of this study show that commitment is a contributing factor to the concept of teamwork. In addition, the study has also managed to portray the actual reality behind the concept of teamwork which is practiced by a leading Bumiputera company that has successfully marketed its products through teamworking. Sample of the study involves 144 entrepreneurs who have been awarded by Syarikat HPA. The selected respondents are a mixture of both ordinary entrepreneurs, and those who hold ranks in the al-Wahida organization throughout Malaysia